Posterobasal left ventricular aneurysm after myocardial infarction with normal coronary arteries: Case-report - Kalinin, Roman Evgenyevich (World J Clin Cases, 2018)
We present a case of a 64-year-old woman with signs of debilitating condition including anginal chest pain, exertional dyspnea, and depression. The patient had previously suffered from a myocardial infarction after a loss of a close family member. Workup showed a posterobasal left ventricular aneurysm and moderate to severe mitral regurgitation in the absence of coronary atherosclerosis. Routine ultrasonography revealed abdominal aortic aneurysm and intraabdominal aortic deviation. The patient was immediately started on optimal medical treatment. On repeat assessment general condition was satisfactory, vital signs were normal, and investigations showed no signs of progressive heart failure or other significant clinical changes. Although prognosis in patients with myocardial infarction with normal coronary arteries is generally considered favorable, mechanical complications such as posterobasal left ventricular aneurysm with moderate to severe mitral regurgitation are possible.